PENGARUH LKS BERTAMPILAN KOMIK TERHADAP HASIL BELAJAR IPA FISIKA SISWA DALAM PEMBELAJARAN PROBLEM BASED INSTRUCTION MATERI GELOMBANG BUNYI DAN OPTIKA DI KELAS VIII SMPN 3 BUKITTINGGI - Ayu Melisa Putri (Universitas Negeri Padang, 2013)
The background of this research is low of students learning outcome. This is caused bylack of students interest for reading books and learning sources. Moreover, students are not really competent to solve physics problem in daily lifeOne of the ways to solve this problem is by applying learning model which can improve students reading interest. Therefore, a research has been implemented about application of students worksheet comic view on Problem Base Instruction (PBI) learning in grade VIII SMPN 3 Bukittinggi. Populations of quasi experiment research which design randomized control group only design are all of students grade VIII inthat is registered in academic years 2012/2013. Sample of research is selected by Cluster Random Sampling technique. Research outcomes shownthere is an influence of application of students worksheet comic view on Problem Base Instruction (PBI) learning in grade VIII SMPN 3real level 0.05 Keywords: students worksheet, comic views, Problem Based Instruction (PBI) learning